The Impact of Corporate Social Responsibility Information Richness on Trust (Issues in Social and Environmental Accounting (ISEA), 2014)
Corporate Social Responsibility (CSR) is a concept that describes the relationship between company  and society. The way a company portrays corporate ethics and social initiatives can evoke strong positive reactions among consumers. The emergence of Internet creates a new communicating culture and gives an idea for a company to deliver their CSR message. Applying Media Richness Theory (MRT) in CSR message is believed could facilitate trust among consumer. Thus, this study aims to examine the impact of different level of CSR information richness with consumers trust towards the company. This study divides trust into three components that are competence, benevolence and integrity. An experimental design consisting of different levels of CSR information is selected (rich CSR information, lean CSR information and no CSR information as a control condition). The finding shows that rich CSR information has impacted on competence and integrity but not on benevolence. Result from this study is believed can assist companies in setting up their CSR communicating strategy in engaging consumers’ trust.